Doing Nonideal Theory About Gender in Global Contexts: A Reply to McLaren, Meyers, and Monque. - Khader, Serene J. (Metaphilosophy, 2021)
This paper elaborates and renders explicit some of the views about political philosophical methodology that underlie the author's arguments in Decolonizing Universalism: A Transnational Feminist Ethic. It shows how the author's stances on autonomy, individualism, intersectionality, human rights, the coloniality of gender, and the oppression of genders besides man and woman grow out of a commitment to scrutinizing our normative views in light of transnational criticism and empirical information from the qualitative social sciences.